2011
DOI: 10.1186/1471-2318-11-19
|View full text |Cite
|
Sign up to set email alerts
|

Study of Mental Activity and Regular Training (SMART) in at risk individuals: A randomised double blind, sham controlled, longitudinal trial

Abstract: BackgroundThe extent to which mental and physical exercise may slow cognitive decline in adults with early signs of cognitive impairment is unknown. This article provides the rationale and methodology of the first trial to investigate the isolated and combined effects of cognitive training (CT) and progressive resistance training (PRT) on general cognitive function and functional independence in older adults with early cognitive impairment: Study of Mental and Regular Training (SMART). Our secondary aim is to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
41
0
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 48 publications
(42 citation statements)
references
References 62 publications
0
41
0
1
Order By: Relevance
“…Some have suggested the implementation of resistance training programs since they have a better potential for long-term adherence than aerobic exercise. 30 The high number of dropouts that we observed once the intervention started were mainly related to death, serious medical events and individuals moving to different areas of the country; the dropouts were not related to the exercise program itself. Other studies performed in elderly subjects with dementia also reported a significant proportion of dropouts due to complications, hospital admissions and deaths, all of which are common events occurring in these frail populations.…”
Section: Discussionmentioning
confidence: 90%
“…Some have suggested the implementation of resistance training programs since they have a better potential for long-term adherence than aerobic exercise. 30 The high number of dropouts that we observed once the intervention started were mainly related to death, serious medical events and individuals moving to different areas of the country; the dropouts were not related to the exercise program itself. Other studies performed in elderly subjects with dementia also reported a significant proportion of dropouts due to complications, hospital admissions and deaths, all of which are common events occurring in these frail populations.…”
Section: Discussionmentioning
confidence: 90%
“…Goal oriented rehabilitation was seen as a clinically effective intervention for early stages of Alzheimer disease, vascular or mixed dementia, and a multi-centre study is ongoing [12].Studies are investigating the dual effects of cognitive training and progressive resistance training to capture the combined impact of physical and cognitive variables [13]. A seven week program (Cognitive Stimulation Therapy) was shown to be beneficial; however, there was less conclusive evidence for the effects of this therapy over an extended period prompting another study with the addition of 16 weeks of maintenance.…”
Section: Introductionmentioning
confidence: 99%
“…Zur Zeit läuft die SMART Studie, die als randomisierte, doppelblinde, place bokontrollierte longitudinale Studie ver sucht, die Wirkung von kognitivem und körperlichem Training auf Menschen mit frühen Anzeichen einer Demenz zu be weisen [16].…”
Section: Introductionunclassified